An alternative approach to cat’s epilepsy treatment – Case report - Liliana Cărpinișan; Laura Rațiu; Janos Degi; Alina Ghișe (Medicamentul Veterinar, 2013)
Angel, a female British Shorthair cat, would be euthanized at the recommendation of three veterinarians, after she manifested epileptic seizures starting from seven months old. Due to her owner and one veterinarian love and effort, she well passed through many seizures and a non-regenerative anemia episode and she survived for five years from the onset of the disease. The mineral-vitamin supplements improved the life quality for four years and the homeopathic therapy successfully removed the seizures for one more year.